Hubungan Usia Dan Jenis Kelamin Dengan Mortalitas Pada Pasien Dengan Luka Berat - Amanda Ayu Lestari; Setyo Trisnadi (PT. Hasba Edukasi Mandiri, 2026)
Serious injuries are a type of injury that has little hope of healing or can be life-threatening. Age and gender in serious injuries increase the risk of patient death. The purpose of this study was to determine the relationship between age and gender with mortality in patients with serious injuries based on Visum et Repertum. This study design was an observational analytic with a cross-sectional design with sampling using the all sampling technique. The sample in this study was 56 samples that met the inclusion criteria including victims of serious injuries and recorded in VeR. This research data was obtained from Visum et Repertum for the period June 2024 - August 2025. Data were analyzed using the Fisher Exact test. Most victims with serious injuries at Bhayangkara Hospital were in the age range of 17-65 years (30 (62.5%) with male gender 33 (66.0%). The results of the Fisher Exact test obtained a p value = 0.698 (p>0.05) for the age variable and a p value = 0.030 (p<0.05) for the gender variable. There is a relationship between gender and mortality. There was no association between age and mortality in victims with serious injuries at Prof. Awaloedin Djamin Bhayangkara Hospital in Semarang City. Males and those aged 17-65 years were more likely to die.